Histone deacetylase inhibitor during in vitro maturation decreases developmental capacity of bovine oocytes - Pontelo, Thais Preisser (PLoS One, 2021)
This study aimed to evaluate the effect of scriptaid during pre-maturation (PIVM) and/or maturation (IVM) on developmental competence of bovine oocytes. Cumulus-oocyte complexes (COCs) were submitted to PIVM for 6 h in the presence or absence of scriptaid. COCs were distributed into five groups: T1-IVM for 22 h, T2-PIVM for 6 h and IVM for 22 h, T3-PIVM with scriptaid for 6 h and IVM for 22 h, T4-PIVM for 6 h and IVM with scriptaid for 22 h, and T5-PIVM with scriptaid for 6 h and IVM with scriptaid for 22 h. Nuclear maturation, gene expression, cumulus cells (CCs) expansion, and embryo development and quality were evaluated. At the end of maturation, all groups presented the majority of oocytes in MII (P>0.05). Only HAT1 gene was differentially expressed (P<0.01) in oocytes with different treatments. Regarding embryo development at D7, T4 (23%) and T5 (18%) had lower blastocyst rate (P<0.05) than the other treatments (T1 = 35%, T2 = 37% and T3 = 32%). No effect was observed when scriptaid in PIVM was used in less competent oocytes (P>0.05). In conclusion, presence of scriptaid in PIVM and/or IVM did not improve developmental competence or embryo quality.